ANALISA PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN - Rini Susilowati; Mira Veranita (EKBIS (Ekonomi & Bisnis), 2020)
The purpose of this study was to determine the effect of service quality on patient satisfaction at RSUD Sumedang. The author uses a case study method with a quantitative descriptive approach through a questionnaire distributed to 50 respondents. The results showed that the services at RSUD Sumedang were good and according to the expectations of the patients, namely by simultaneously providing good services in various sectors. Patient satisfaction reaches 80% of the expectations they want, this shows that patients are satisfied with the quality of service at RSUD Sumedang. The spearman rank correlation calculation shows a strong correlation, namely 0.629 between indicators of tangibles, reliability, responsiveness, assurance and empathy with patient satisfaction. Patient satisfaction is influenced by the quality of service by 39.5% and the rest is influenced by other factors that the authors did not examine.